The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3389/fneur.2017.00535
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Fungi in the Etiology of Multiple Sclerosis

Abstract: Multiple sclerosis (MS) is a chronic inflammatory disorder of the central nervous system. Infectious triggers of MS are being actively investigated. Substantial evidence supports the involvement of the Epstein-Barr virus (EBV), though other viruses, bacteria, protists, and fungi are also being considered. Many links between fungi and diseases involving chronic inflammation have been found recently. Evidence linking MS and fungi is reviewed here. The HLA-DRB1*15 allele group is the most important genetic risk f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 143 publications
(183 reference statements)
0
28
0
Order By: Relevance
“…Very recently, it was shown in a mouse model that chronic transient candidemia, while being cleared quickly from the circulation, led to highly localized cerebritis that, in the long term, could lead to substantial neuronal loss and progressive cognitive impairment [17]. There is also emerging but still limited evidence that the gut mycobiome is intricately involved in neurological disease and that fungal components may play a role in Alzheimer disease and multiple sclerosis [18][19][20]. For PLWH on suppressive ART, it has been shown that βDG was detectable in CSF, with a trend toward higher CSF βDG levels in individuals with neurocognitive impairment [21].…”
mentioning
confidence: 99%
“…Very recently, it was shown in a mouse model that chronic transient candidemia, while being cleared quickly from the circulation, led to highly localized cerebritis that, in the long term, could lead to substantial neuronal loss and progressive cognitive impairment [17]. There is also emerging but still limited evidence that the gut mycobiome is intricately involved in neurological disease and that fungal components may play a role in Alzheimer disease and multiple sclerosis [18][19][20]. For PLWH on suppressive ART, it has been shown that βDG was detectable in CSF, with a trend toward higher CSF βDG levels in individuals with neurocognitive impairment [21].…”
mentioning
confidence: 99%
“…HLA-DRB1 allele, which is the most important genetic risk factor for MS, is associated with fungal infections. Many cytokines and markers involved in fungal infection such as interleukin 17, chitotriosidase and antibodies against fungus are also involved in MS disease and can be pathogenic 44 . In relation to the diet, the conducted experiments prevented people with MS from a high-fat diet, high in cholesterol, sugar, and sodium, to prevent the exacerbation of disease symptoms 38 .…”
Section: Discussionmentioning
confidence: 99%
“…While the existence of an as-yet-unrecognized genital infection may seem to be far-fetched at first, such a hypothesis has been proposed to explain the sexual risk factors of multiple sclerosis ( 9 , 14 ) and prostate cancer ( 7 , 8 , 13 ) based on evidence completely unrelated to spondyloarthritis (Table 4 ). Recent studies have implicated fungal infections in multiple sclerosis ( 5 , 206 208 ) and prostate cancer ( 4 , 15 , 172 ), and these infections appear to be intracellular in both cases (Table 4 ) ( 4 , 209 , 210 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, circulating CD4+ T cells in uveitis patients are more sensitive than controls to fungal antigens ( C. albicans ) after a 24-h antigen exposure period ( 127 ), whereas sensitivity to bacterial antigens ( Staphylococcus aureus, Clostridium tetani , and Mycobacterium tuberculosis ) and protist antigens ( Toxoplasma gondii ) are similar in both groups ( 127 ). Intermediate uveitis is associated with multiple sclerosis onset ( 128 ) and with the HLA-DRB1*1501 allele ( 129 ), which are both associated with the immune response to fungi ( 5 ). A small study reported that oral dimethyl fumarate, a fungicidal compound known to be effective in multiple sclerosis and psoriasis, improved chronic idiopathic uveitis symptoms in four patients ( 130 ).…”
Section: Links With Fungimentioning
confidence: 99%
See 1 more Smart Citation